On some results for ?-spiral functions of order a - Milutin Obradovic; Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
The results of various kinds concerning ?-spiral functions of order a in the unit disk U are given in this paper. They represent mainly the generalizations of the previous results of the authors.